Evaluación del grado de abrasividad de cremas dentales comerciales en Colombia sobre la superficie del esmalte en dientes de bovino. - Pinto, Omar; Gómez, Belkis Tatiana; Rojas, María Paula (Universidad Antonio Nariño, 2021)
Objective: Evaluate the abrasive effects of the toothpastes selected for the investigation, on the morphology of the surface of bovine tooth enamel. Materials and Methods: 15 bovine teeth which were divided into 3 groups (A, B, C). Where group A corresponded to (Colgate luminous white), group B (Optifresh Sistem 8), group C (Colgate total 12). This was brushed on the vestibular surface using the Oral b Professional Care 5000 electric toothbrush, 3 times a day for 2 minutes for 15 days. After the teeth are subjected to the action of each cream, these were evaluated using scanning electron microscope. Results: It was found that the toothpastes used in the research, generate an abrasive effect on the surface of the tooth enamel after tooth brushing for 15 days 3 times a day. Conclusion: Taking into account the results obtained in the study, we determined that the use of an electric toothbrush in company with commercial toothpastes in Colombia can generate an abrasive effect on the enamel surface, thus generating dentinal hypersensitivity.